The Influence of Organizational Culture and Training on Employee Performance in the Kana Kuta Bali - Sumerta, I Ketut Eli (Akademi Komunitas MAPINDO, 2024)
The purpose of this study was to determine the effect of organizational culture and training on employee performance at The Kana Kuta Bali. The population of this study were all employees at The Kana Kuta Bali, namely 49 people. Data collection techniques in this study were observation, questionnaires, interviews, and documentation. The data analysis techniques used are descriptive analysis, data quality test, classical assumption test, multiple linear regression analysis, and hypothesis testing using SPSS version 23. Based on the results of the analysis, it is known that: (1) Organizational culture has a positive and significant effect partially on employee performance, where the t-count value is 2.551> t-table 1.678 with a significance value of 0.014 whose value is <0.05. (2) Training has a positive and significant effect partially on employee performance, where the t-count value is 2.050> t-table 1.678 with a significance value of 0.046 whose value is <0.05. (3) From the results of the F test, the results obtained a simultaneous positive and significant effect between organizational culture and training on employee performance, the value of F-count = 27.109> F-table = 3.20 with a significance value of F of 0.000, whose value is <0.05.